EVALUATING SOUTH AFRICAN CHENIN BLANC WINE STYLES USING AN LC-MS SCREENING METHOD - BUICA, Astrid; BRAND, Jeanne; WILSON, Christine; STANDER, Marietjie (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Sensory evaluation is the approach currently used when evaluating the style of a South African Chenin Blanc wine. Using an untargeted LC-HRMS approach, a number of wine samples previously attributed to the three recognized styles were used to build a statistical model which was further used to predict to which style group additional samples belonged. This application can be considered proof-of-principle.